Foreword - Wriston, Walter B. (Tufts Archival Research Center, 2007)
This document was created from the Foreword written by Walter B. Wriston for the book "Citibank: 1812-1970" by Harold van B. Cleveland and Thomas F. Huertas in 1985. The original foreword is located in MS134.003.026.00020.